Comparison of outcomes: scleral buckling and pars plana vitrectomy versus vitrectomy alone for primary repair of rhegmatogenous retinal detachment - Lindsell LB; Sisk RA; Miller DM; Foster RE; Petersen MR; Riemann CD; Hutchins RK (Clinical Ophthalmology, 2016)
Luke B Lindsell, Robert A Sisk, Daniel M Miller, Robert E Foster, Michael R Petersen, Christopher D Riemann, Robert K Hutchins Cincinnati Eye Institute, Department of Ophthalmology, University of Cincinnati, Cincinnati, OH, USA Objective: To assess the combination of scleral buckling (SB) and pars plana vitrectomy (PPV) versus PPV alone in the primary repair of rhegmatogenous retinal detachments (RRDs).Methods: The current study was a retrospective, comparative, interventional, consecutive case series of 179 eyes of 174 patients who underwent primary RRD repair by five surgeons between January 1, 2008 and December 31, 2010, utilizing SB with PPV or PPV. Univariate and multivariate analyses were used to compare the efficacy of the two surgical strategies and assess for risk factors of proliferative vitreoretinopathy (PVR).Results: Single surgery anatomic success (SSAS) was similar (P=0.76) between the PPV group (112 of 132 eyes, 85%) and SB with PPV group (39 of 47 eyes, 83%). Final anatomic success was 100% in each group. There was no difference in rates of PVR formation (PPV 16% vs SB with PPV 19%, P=0.70). Final logarithm of the minimum angle of resolution acuity was 0.33 (20/43) in the PPV group and 0.37 (20/47) in the SB with PPV group (P=0.62). Postoperative anterior chamber fibrin was highly correlated with PVR formation (PVR 13% vs no PVR 0.7%, P=0.003; odds ratio =68.37, P=0.007). Separate analysis of medium- to high-complexity cases showed similar SSAS (PPV 86% vs SB with PPV 83%, P=0.45).Conclusion: SB with PPV versus PPV alone were similarly efficacious for repair of primary RRDs of varying complexity. SSAS rates, PVR incidence, and final visual acuities were not significantly different. Keywords: scleral buckling, vitrectomy, rhegmatogenous retinal detachment, outcomes, proliferative vitreoretinopathy, comparison